Antibiotic resistance and molecular characterization of clinical isolates of methicillin-resistant coagulase-negative staphylococci isolated from bacteremic patients in oncohematology - Bouchami, O; Achour, W; Mekni, M. A; Rolo, J; Ben Hassen, A (Folia microbiologica, 2011)
Polymerase chain reaction (PCR) amplification of antibiotic resistance genes as well as staphylococcal cassette chromosome mec (SCCmec) typing and pulsed-field gel electrophoresis (PFGE) of SmaI macrorestriction fragments of genomic DNA were used to characterize 45 methicillin-resistant coagulase-negative staphylococci (MRCoNS) isolates responsible of bacteremia recovered in patients at the Bone Marrow Transplant Centre of Tunisia in 1998-2007. Among the 45 MRCoNS isolates, Staphylococcus epidermidis was the most prevalent species (75.6%) followed by Staphylococcus haemolyticus (22.2%) and Staphylococcus hominis (2.2%). Extended susceptibility profiles were generated for MRCoNS against 16 antimicrobial agents. Out of 45 mecA-positive strains, 43 (95.6%) were phenotypically methicillin-resistant and two (4.4%) were methicillin-susceptible. The msr(A) was the most prevalent gene (13 isolates; 48.1%) among erythromycin-resistant isolates. The erm(C) was found alone in seven (25.9%) or in combination with both erm(A) and erm(B) in two (7.4%) isolates. The aac(6')-Ie-aph(2″)-Ia was the most prevalent gene among aminoglycoside-resistant isolates, detected alone in 14 isolates (33.3%) isolates, in combination with ant(4')-Ia in 18 (42.8%) isolates, in combination with aph(3')-IIIa in four (9.5%) or with both ant(4')-Ia and aph(3')-IIIa in two (4.7%) isolates. The ant(4')-Ia was detected in three (7.1%) isolates and the aph(3')-IIIa in one (2.4%) isolate. Among tetracycline-resistant isolates, six (85.7%) strains harbored the tet(K) gene and one (14.3%) strain carried tet(K) and tet(M) genes. SCCmec types IV (31%) and III (24.5%), the most prevalent types detected, were found to be more resistant to non-β-lactam antibiotics. A wide diversity of isolates was observed by PFGE among MRCoNS.
Keywords: pulzní gelová elektroforéza; Molecular Typing; Tunisia; Tunisko; mikrobiální testy citlivosti; polymerázová řetězová reakce; Polymerase Chain Reaction; Staphylococcus haemolyticus; Deoxyribonucleases, Type II Site-Specific; DNA bakterií; bakteriální geny; DNA, Bacterial; Staphylococcus hominis; lidé; Anti-Bacterial Agents; molekulární typizace; Bacteremia; Electrophoresis, Gel, Pulsed-Field; bakteriální léková rezistence; rezistence na methicilin; Staphylococcus epidermidis; bakteriemie; Microbial Sensitivity Tests; stafylokokové infekce; hematologické nádory; Hematologic Neoplasms; restrikční endonukleasy typu II; Bacterial Typing Techniques; techniky typizace bakterií; koagulasa; Genes, Bacterial; Staphylococcal Infections; Methicillin Resistance; Coagulase; antibakteriální látky; Drug Resistance, Bacterial; Humans